2012
DOI: 10.1590/s0102-695x2011005000189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatoprotective activity of aqueous and ethanolic extract of Oxalis corniculata against intoxication of thioacetamide induced rats

Abstract: Abstract:The present study was carried out to evaluate the hepatoprotective activity of aqueous and ethanolic leaves extracts of Oxalis corniculata L., Oxalidaceae, against thioacetamide-induced hepatotoxicity. Hepatotoxicity was induced in Wistar rats of either sex by subcutaneous injection of thioacetamide. .37 IU/L respectively) and total bilirubin (0.226±0.00 mg/dL 0.288±0.01 mg/dL respectively) content that were lesser than positive control, thioacetamide damaged rats. Histology of the liver sections of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…37 IU/L respectively) and total bilirubin (0.226±0.00 mg/dL 0.288±0.01 mg/dL respectively) content that were lesser than positive control, thioacetamide damaged rats. Histology of the liver sections of the animals treated with the extract also showed dose dependent reduction of necrosis 34 .…”
Section: Anti-ulcer Activitymentioning
confidence: 80%
“…37 IU/L respectively) and total bilirubin (0.226±0.00 mg/dL 0.288±0.01 mg/dL respectively) content that were lesser than positive control, thioacetamide damaged rats. Histology of the liver sections of the animals treated with the extract also showed dose dependent reduction of necrosis 34 .…”
Section: Anti-ulcer Activitymentioning
confidence: 80%
“…As per Drotman and Lawhorn [21] increased level of serum enzymes are indicative of cellular leakage and loss of functional integrity of cell membrane in liver. TAA causes significant increase in the level of serum SGOT, SGPT, ALP and Bilirubin which forms liver toxicity [22]. Achliya et al [23] have rightly reported that bilirubin is the conventional indicator of liver diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Sohail et al [62] developed an extraction method with different solvents to reduce the oxalates amount present in this plant. The MeOH extracts of the stem and leaves with a low oxalate content showed a good antioxidant activity in vitro (DDPH and β-carotene linoleate), and showed HPP activity compared against the hepatic damage caused by thioacetamide (aqueous and EtOH extracts) and against CCl 4 (MeOH) [63,64]; therefore, they evaluated the HPP activity in vivo against the OS caused by INH/RIF (100 mg/kg, each) in Wistar rats. The MeOH extract (stems and leaves) was administered orally for 21 days, at 400 mg/kg, using Sil (2.5 mg/kg) as PC.…”
Section: Open Access Freely Available Onlinementioning
confidence: 99%